(1 + cos theta - i * sin theta) ^ n = 2 ^ (n + 1) * (cos theta / 2) ^ n * cos ( n * theta / 2)?

(1 + cos theta - i * sin theta) ^ n = 2 ^ (n + 1) * (cos theta / 2) ^ n * cos ( n * theta / 2)?
Anonim

תשובה:

אנא ראה להלן.

הסבר:

תן # 1 + costheta + isintheta = r (cosalpha + isinalpha) #, כאן # r = sqrt (1 + costheta) ^ 2 + חטא ^ 2theta) = sqrt (2 + 2costheta) # #

= #sqrt (2 + 4cos ^ 2 (theta / 2) -2) = 2cos (theta / 2) # #

ו # tanalpha = sintheta / (1 + costheta) == (2sin (theta / 2) cos (theta / 2)) / (2cos ^ 2 (theta / 2)) = tan (theta / 2) # # או # alpha = theta / 2 #

לאחר מכן # 1 + costheta-isintheta = r (cos (-alpha) + isin (alpha)) r = (cosalpha-isinalpha) #

ואנחנו יכולים לכתוב # (1 + costheta + isintheta) ^ n + (1 + costheta-isintheta) ^ n # באמצעות משפט DE MOVERRE כמו

# r ^ n (cosnalpha + isinnalpha + cosnalpha-isinnalpha) #

= # 2r ^ ncosnalpha #

= # 2 * 2 ^ ncos ^ n (theta / 2) cos ((ntheta) / 2) # #

= # 2 ^ (n + 1) cos ^ n (theta / 2) cos ((ntheta) / 2) # #